Development and Validation of a Nomogram for the Prediction of Inguinal Lymph Node Metastasis Extranodal Extension in Penile Cancer - Wu, Chong; Li, Zaishang; Guo, Shengjie; Zhou, Fangjian; Han, Hui (Frontiers in Oncology, 2021)
Purpose: To determine whether a clinicopathologic and laboratory-based nomogram is able to predict the risk of lymph node extranodal extension (ENE) in patients with penile cancer. Materials and Methods: From June 2006 to January 2021, 234 patients who underwent bilateral inguinal lymph node dissection (ILND) surgery were included in the analysis. A Lasso regression model was used to select the most useful predictive features from among 46 laboratory variables. Then, a logistic regression analysis was used to develop the prediction model. The performance of the nomogram was assessed with respect to its calibration, discrimination, and clinical usefulness. Its internal validation was confirmed. Results: Among the 234 patients, 53 were confirmed to have ENE. The platelet/lymphocyte(PLR) and Squamous cell carcinoma antigen(SCCA) were significantly associated with ENE (P＜0.01). The individualized prediction nomogram, including the PLR, SCC, lymphovascular invasion(LVI), and pathologic tumor stage(pT-stage), showed good discrimination, with a C-index of 0.817 (95% CI, 0.745 to 0.890) and good calibration. Decision curve analysis(DCA) demonstrated that the nomogram was more clinically useful than the pT-stage or tumor grade. Conclusions: This study presents a clinicopathologic and laboratory-based nomogram that incorporates PLR, SCC, LVI, and pT-stage, which can be conveniently used to facilitate the individualized prediction of ENE in patients with penile cancer.